Utilization of Virtual Reality: Transforming Spiritual Experiences in Hajj Ritual Learning in High Schools and Tour Travel - Basri, Hasan (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Secondary hajj education is often abstract and limited to physical simulations that cannot capture the Holy Land's vastness and holiness. The lack of representative Islamic religious education laboratories in Wajo Regency exacerbates this. Viewing rituals as physical procedures without inner transformation or Mecca and Medina spatial awareness lowers student spiritual engagement. This study examines how VR technology and PT Darmawan Tour & Travel can improve Wajo Regency high school students' Hajj practices and how digital immersion connects cognitive theory and affective-spiritual experiences. This study employs descriptive qualitative and collaborative case study methods. The study utilized VR devices and PT Darmawan Tour & Travel content in Wajo Regency high schools. Data is collected through participatory observation during VR simulations, in-depth interviews with professors of Islamic Religious Education and Hajj and focus group discussions (FGDs) with students. To measure spiritual presence, data reduction, presentation, and verification were done. The research indicated that VR's "real presence" effect on Hajj rituals evoked high emotional responses, such as emotion and commitment, not found in simulations. PT Darmawan Tour & Travel ensured field-relevant visual and procedural accuracy. Students claimed a better grasp of the pilgrimage itinerary and enhanced religious enthusiasm to perform Hajj. VR can create immersive spiritual places in schools. This paper proposes a VR-based experiential learning methodology for Islamic religious education. This article advocates for a strategic alliance between educational institutions and Hajj travel agencies to enhance religious education resources and urges Wajo Regency education authorities to incorporate immersive technology into the regional curriculum.